Robotic technology in cardiovascular medicine - Bonatti, Johannes; Vetrovec, George; Riga, Celia; Wazni, Oussama; Stadler, Petr (Nature reviews. Cardiology, 2014)
Robotic technology has been used in cardiovascular medicine since the late 1990s. Interventional cardiology, electrophysiology, endovascular surgery, minimally invasive cardiac surgery, and laparoscopic vascular surgery are all fields of application. Robotic devices enable endoscopic reconstructive surgery in narrow spaces and fast, very precise placement of catheters and devices in catheter-based interventions. In all robotic systems, the operator manipulates the robotic arms from a control station or console. In the field of cardiac surgery, mitral valve repair, CABG surgery, atrial septal defect repair, and myxoma resection can be achieved using robotic technology. Furthermore, vascular surgeons can perform a variety of robotically assisted operations to treat aortic, visceral, and peripheral artery disease. In electrophysiology, ablation procedures for atrial fibrillation can be carried out with robotic support. In the past few years, robotically assisted percutaneous coronary intervention and abdominal aortic endovascular surgery techniques have been developed. The basic feasibility and safety of robotic approaches in cardiovascular medicine has been demonstrated, but learning curves and the high costs associated with this technology have limited its widespread use. Nonetheless, increased procedural speed, accuracy, and reduced exposure to radiation and contrast agent in robotically assisted catheter-based interventions, as well as reduced surgical trauma and shortened patient recovery times after robotic cardiovascular surgery are promising achievements in the field.
Keywords: Robotics; kardiovaskulární nemoci; Humans; lidé; kardiochirurgické výkony; Cardiovascular Diseases; Cardiac Surgical Procedures; Treatment Outcome; výsledek terapie; robotika